2023
DOI: 10.1007/s11356-023-26941-2
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl substance (PFAS) exposure and risk of nonalcoholic fatty liver disease in the elderly: results from NHANES 2003–2014

Abstract: This study aimed to investigate the association between PFASs exposure and the risk of NAFLD in the elderly. Our sample included 1420 participants (≥ 60 years) from the 2003-2014 NHANES study with available serum PFASs, covariates and outcomes. NAFLD was de ned based on the hepatic steatosis index. Weighted binary logistic regression was utilized to calculate the odds ratio (OR) and 95% con dence intervals for each chemical. Results suggested that each one unit increase in ln-transformed concentration of PFOA … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
6
5
0
Order By: Relevance
“…Remarkably, CYP4A11 up-regulation has been associated with non-alcoholic fatty liver disease (NAFLD), since it increases the intracellular production of reactive oxygen species (ROS) and pro-inflammatory cytokines [70]. Our result is in line with data showing that exposure to PFOA is positively related to NAFLD development [71]. The other upregulated genes (Figure 2B) are mainly implicated in lipid metabolism, mitochondrial function, and stress response, while downregulated genes participate in immune response and inflammation, thrombosis, and cellular adhesion.…”
Section: Correlation Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…Remarkably, CYP4A11 up-regulation has been associated with non-alcoholic fatty liver disease (NAFLD), since it increases the intracellular production of reactive oxygen species (ROS) and pro-inflammatory cytokines [70]. Our result is in line with data showing that exposure to PFOA is positively related to NAFLD development [71]. The other upregulated genes (Figure 2B) are mainly implicated in lipid metabolism, mitochondrial function, and stress response, while downregulated genes participate in immune response and inflammation, thrombosis, and cellular adhesion.…”
Section: Correlation Analysissupporting
confidence: 88%
“…The relationship between dyslipidemia and PFAS has also been found in human children and adolescents [78], where the exposure to these chemicals increases the risk of developing NASH and NAFLD [79] as well as impairing glucose metabolism [105]. Notably, we found that CYP4A11, previously associated with NAFLD [70,71], is highly up-regulated in both humans and mice, possibly indicating a causative role in NASH development due to PFAS exposure. The impact of PFAS on children is a crucial issue, and it seems that these chemicals can even be transferred through breastfeeding [17,18], which is of great concern.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Remarkably, CYP4A11 up-regulation has been associated with non-alcoholic fatty liver disease (NAFLD), since it increases the intracellular production of reactive oxygen species (ROS) and pro-inflammatory cytokines [72]. Our result is in line with data showing that exposure to PFOA is positively related to NAFLD development [73]. The other upregulated genes (Figure 2B) are mainly implicated in lipid metabolism, mitochondrial function, and stress response, while downregulated genes participate in immune response and inflammation, thrombosis, and cellular adhesion.…”
Section: Correlation Analysissupporting
confidence: 88%
“…The relationship between dyslipidemia and PFAS has also been found in human children and adolescents [80], where the exposure to these chemicals increases the risk of developing NASH and NAFLD [81] as well as impairing glucose metabolism [106]. Notably, we found that CYP4A11, previously associated with NAFLD [72,73], is highly up-regulated in both humans and mice, possibly indicating a causative role in NASH development due to PFAS exposure. The impact of PFAS on children is a crucial issue, and it seems that these chemicals can even be transferred through breastfeeding [17,18], which is of great concern.…”
Section: Discussionsupporting
confidence: 64%